2020
DOI: 10.1186/s13619-020-00047-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mesenchymal stem cell-conditioned medium in bone regeneration in animal and human models: a systematic review and meta-analysis

Abstract: Background Given the limitations of current therapies for the reconstruction of bone defects, regenerative medicine has arisen as a new therapeutic strategy along with mesenchymal stem cells (MSCs), which, because of their osteogenic potential and immunomodulatory properties, have emerged as a promising alternative for the treatment of bone injuries. In vivo studies have demonstrated that MSCs have a positive effect on regeneration due to their secretion of cytokines and growth factors that, when collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…Cell-induced and particularly stem cell treatment has become a potential therapeutic method for incurable diseases. For stem cell-based therapy, MSCs have attracted much attention [44] , [45] . MSCs are pluripotent stem cells originating from placenta, umbilical blood and bone marrows in autologous and allogenic sources, widely used for viral diseases including acute lung injury (ALI) in influenza, chronic hepatitis in hepatitis B virus (HBV) and HIV [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Cell-induced and particularly stem cell treatment has become a potential therapeutic method for incurable diseases. For stem cell-based therapy, MSCs have attracted much attention [44] , [45] . MSCs are pluripotent stem cells originating from placenta, umbilical blood and bone marrows in autologous and allogenic sources, widely used for viral diseases including acute lung injury (ALI) in influenza, chronic hepatitis in hepatitis B virus (HBV) and HIV [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MSCs, MSC-CM and other cell-based therapies in bone regeneration are also under investigation. Maria 38 and Augustine 2 concluded that the application of MSC-CM to treat bone defects had a favorable effect on the repair and regeneration of bone tissue. This finding suggests that paracrine effects are of great importance in MSC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-CM has a promising prospect to be produced as pharmaceuticals in accelerating wound healing [ 4 ]. A major issue of using MSC-CM is the low concentrations of growth factors and anti-inflammatory cytokines in CM for effective therapy [ 16 ]. Several strategies of using MSC-CM were designed to increase the release of the proper molecules for optimal wound healings such as PDGF, VEGF, and IL-10 with high levels.…”
Section: Introductionmentioning
confidence: 99%